2016
DOI: 10.9758/cpn.2016.14.4.402
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil Dependence and Hypersexuality: A Case Report and Review of the Evidence

Abstract: Apart from sleep wake disorders, nowadays, modafinil is being prescribed for several psychiatric disorders including depression. Despite being reported as to be having very low abuse potential, cases of modafinil dependence had come to the limelight. In this case report, we describe a 35 year old man with bipolar affective disorder while in remission who developed modafinil dependence and later on, had hypersexuality when he increased the dose of modafinil from 400 to 1,000 mg/day. Existing literature suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, our and other findings emphasize that when taken at higher doses, such as in recreational use, modafinil could have abuse potential in humans. In fact, two recent case report studies have described that patients who started treatment with modafinil with increasing doses reported withdrawal symptoms similar to those experienced during abstinence of psychostimulant drugs upon discontinuation of modafinil ( Swapnajeet et al, 2016 ; Alacam et al, 2018 ).…”
Section: Discussionmentioning
confidence: 98%
“…However, our and other findings emphasize that when taken at higher doses, such as in recreational use, modafinil could have abuse potential in humans. In fact, two recent case report studies have described that patients who started treatment with modafinil with increasing doses reported withdrawal symptoms similar to those experienced during abstinence of psychostimulant drugs upon discontinuation of modafinil ( Swapnajeet et al, 2016 ; Alacam et al, 2018 ).…”
Section: Discussionmentioning
confidence: 98%
“…Upsurge of dopamine in the mesolimbic pathway after a supratherapeutic dosage of modafinil might explain for the development of hypersexuality in this case, although the exact pathophysiological mechanism is unknown. 194 Lastly, a 23-year old man with methamphetamine dependence history was prescribed modafinil 200 mg as an adjunctive treatment for daytime hypersomnolence and fatigue associated to methamphetamine withdrawal. The patient was admitted 6 months later with a methamphetamine induced psychosis and he had also been using modafinil at a self-increased dose of 400 mg per day .…”
Section: Abuse Potential Dependence and Withdrawalmentioning
confidence: 99%
“…The withdrawal symptoms are mostly nonspecific and subsided when the dose is decreased in a controlled environment. 191 , 192 , 194 On the other hand, at recommended doses it has not shown the propensity to produce dependence, tolerance and withdrawal like those associated with chronic amphetamine and cocaine use. 62 , 118 Modafinil should be prescribed cautiously, and clinicians should be aware of its possible abuse potential if used incorrectly, especially in patients with psychiatric disorders or with a history of drug abuse.…”
Section: Abuse Potential Dependence and Withdrawalmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, differences have been reported in the whole brain, cortical thickness (CTh), lobar volumes, grey and white matter volumes, corpus callosum size and connectivity profiles, and it is shown that they are correlated with distinctive cognitive abilities of males and females regarding visuospatial processing and language. 1 8) Motivated by this category of studies, many researchers have attempted to investigate the human brain in the gender identity disorder or more recently in gender dysphoria (GD) in the past few years (actually, GD replaced gender identity disorder since the publication of the 5th edition of the DSM in 2013). Individuals with GD are called transgender and they often feel an emotional and social pressure.…”
Section: Introductionmentioning
confidence: 99%